Afrontamiento Escolar y Rendimiento Académico en Los estudiantes de la Unidad Educativa "Pedro Vicente Maldonado". Riobamba. Marzo-Julio. 2017 - Bejarano Minta, Aurelio Fernando (2018)
This research is based on the problems of resistancc that studcnts present in an acaclemic performance, which guicle the work cletcrmining thc conílict a11CI its relation with the cducatioual arrangement of the stuclents ar the first of the parallel baccalaureate A of the "Pedro Vicente Maldonado" Educational l J nil. Riobamba March-August 201 7. Methoclologically, thc clcsign is of a non-experimental, field type, by the cliagnostic cxplorution lcvel, the scientific methocl was appliecl through the Deductive - lnductive proccss, it was clone with a population of 35 stuclents of the first year of high school . thc sample was random and intcntional, thc tcchniquc usecl for the inclepcnclcnt variable in thc l'sychometric Test. Scale Aes. which ictcntifics the different peclagogical stratcgies of thc aclolesccnts, for thc dcpcndcnt variable. thc stuclcnts' grades wcrc takcu as rcfercncc. Thcrc may be an agrccmcnt according to thc rcsults that there may be a relationship betwccn rcsistance aud academ ic performance,